1991
DOI: 10.1002/chir.530030611
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of diastereomeric amino acids with o‐phthaldialdehyde

Abstract: The kinetics of the reaction of the amino acid epimers L-isoleucine, D-allo-isoleucine, L-threonine, and D-allo-threonine with o-phthaldialdehyde and mercaptoethanol were determined at 25 degrees C. L-Isoleucine reacts faster than its D-epimer whereas L-threonine reacts slightly slower than its D-epimer. In the case of isoleucine, the consequence can be an allo/iso ratio which in the worst case is 25% too low if these amino acids are quantified by liquid chromatography and o-phthaldialdehyde fluorescence detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Using the reagent containing OPA and 2-ME it was possible to distinguish epimers, diastereoisomeric amino acids, based on differences in the rates of reactions yielding the fluorescent product …”
Section: 14 Structures Of Amino Acids and Aminesmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the reagent containing OPA and 2-ME it was possible to distinguish epimers, diastereoisomeric amino acids, based on differences in the rates of reactions yielding the fluorescent product …”
Section: 14 Structures Of Amino Acids and Aminesmentioning
confidence: 99%
“…Under such conditions the reaction resulting in formation of the adduct proceeds rapidly and the highest concentration of the fluorescent adduct is reached within minutes or their fractions. Therefore, studies of the initial stage of this reaction were carried out using stop-flow technique. ,,, To follow the reaction, more recently ,− special spectrophotometric techniques enabling rapid measurement of absorbance instead of following the fluorescence have been introduced.…”
Section: 4 Kinetics Of the Formation Of The Primary Productmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinetic data on the OPA reaction of the common amino acids have been published by Svedas et al [24] and Meyer et al [25]. It was shown that the reaction is second order in the amino acid and OPA concentrations, with rate constants between 20 and 100 mol-lls -1 for most amino acids.…”
Section: Kinetics Of the Opa Reactionmentioning
confidence: 98%
“…Measurements of the intensity of fluorescence of the species resulting in the reaction of OPA in the presence of a thiol with AAs has been widely used in chromatographic and flow-injection analyses as examples of the large number of reported applications can attest (Meyer et al 1991;Svedas et al 1978;Qureshi 1987;Ashman and Bosserhoff 1985;Joseph and Davies 1983;Allison et al 1984;Oka et al 1984;Kim 1987;Forster and Marsden 2001). In chromatography, the reaction can be used either in the pre-column or post-column derivatization.…”
mentioning
confidence: 99%